Pengaruh Media Latihan Gaya Pegas Terhadap Hasil Kecepatan Tendangan Mawashi Geri Atlet Shoto-Kai Kota Bengkulupengaruh Media Latihan Gaya Pegas Terhadap Hasil Kecepatan Tendangan Mawashi Geri Atlet Shoto-Kai Kota Bengkulu - Dian Pujianto; Ema Saputri; syafrial (SPORT GYMNASTICS : Jurnal Ilmiah Pendidikan Jasmani, 2022)
ABSTRACT EMA SAPUTRI : The effect of spring force training media on the results of the mawashi geri kick speed of Shoto-kai athletes in Bengkulu City. Thesis. Bengkulu: Physical Education Study Program, FKIP, Bengkulu University, 2022. This study aims to determine the effect of the spring force training media on the results of the mawashi geri kick speed of Shoto-kai athletes in Bengkulu City. This study has used quantitative research with an experimental design method of one group pretest posttest. Data collection techniques with tests and measurements. Mawashi geri kick instrument. The population in this study was 115 athletes while the sample in this study was 30 athletes. The results of data analysis, description, testing of research results, and discussion, it can be concluded that there is a significant effect between training using spring force training media on the results of the mawashi geri kicking speed of Shoto-kai athletes in Bengkulu City, with an increase of (20,32 %). And the result of tcount 12.5 > ttable 1.699. Based on the results of the study, it can be concluded that the exercise method using the spring force has an effect on the results of the mawashi geri kick speed of Shoto-kai athletes in Bengkulu City. Keywords: Spring Style, Mawashi Geri Kick, Karate ABSTRACTEMA SAPUTRI : The effect of spring force training media on the results of the mawashi geri kick speed of Shoto-kai athletes in Bengkulu City. Thesis. Bengkulu: Physical Education Study Program, FKIP, Bengkulu University, 2022.This study aims to determine the effect of the spring force training media on the results of the mawashi geri kick speed of Shoto-kai athletes in Bengkulu City. This study has used quantitative research with an experimental design method of one group pretest posttest. Data collection techniques with tests and measurements. Mawashi geri kick instrument. The population in this study was 115 athletes while the sample in this study was 30 athletes. The results of data analysis, description, testing of research results, and discussion, it can be concluded that there is a significant effect between training using spring force training media on the results of the mawashi geri kicking speed of Shoto-kai athletes in Bengkulu City, with an increase of (20,32 %). And the result of tcount 12.5 > ttable 1.699. Based on the results of the study, it can be concluded that the exercise method using the spring force has an effect on the results of the mawashi geri kick speed of Shoto-kai athletes in Bengkulu City.Keywords: Spring Style, Mawashi Geri Kick, Karate